Workshop on Transformative Technologies in Agriculture: Notes to participants - Mason-D'Croz, Daniel; Herrero, Mario; Peou, Rathana; Thornton, Philip K. (2019)
The challenges facing the global food system to supply sufficient safe and nutritious food for all are considerable. To achieve this goal while also adapting to climate change and trying to reduce the environmental pressures coming from the food system will require a transformation of the food system. Following the findings from a range of high-level analyses, it is recognized that this transformation will need to be systematic and include changes across production practices, diets, and the way the food system produces and manages waste1-5.